2006
DOI: 10.1111/j.1471-4159.2006.03803.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane ion permeability induced by mutant α‐synuclein contributes to the degeneration of neural cells

Abstract: Mutations in a-synuclein cause some cases of familial Parkinson's disease (PD), but the mechanism by which a-synuclein promotes degeneration of dopamine-producing neurons is unknown. We report that human neural cells expressing mutant a-synuclein (A30P and A53T) have higher plasma membrane ion permeability. The higher ion permeability caused by mutant a-synuclein would be because of relatively large pores through which most cations can pass non-selectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0
8

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 30 publications
(44 reference statements)
7
85
0
8
Order By: Relevance
“…Specifically, the His residue located at position 50 in the a-syn monomer is a possible candidate for interaction with Zn 2+ ions because it is situated near the putative pore region of the a-syn pentamer. The increased ion channel activity observed in the present study is in agreement with recent results showing that human neuronal cells expressing mutant a-syn have high plasma membrane ion permeability that was sensitive to calcium chelators [47]. Taken together, these results support the contention that a-syn aggregates might form functional ion-permeable channels that in turn might play a role in the mechanisms of neurodegeneration in LBD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, the His residue located at position 50 in the a-syn monomer is a possible candidate for interaction with Zn 2+ ions because it is situated near the putative pore region of the a-syn pentamer. The increased ion channel activity observed in the present study is in agreement with recent results showing that human neuronal cells expressing mutant a-syn have high plasma membrane ion permeability that was sensitive to calcium chelators [47]. Taken together, these results support the contention that a-syn aggregates might form functional ion-permeable channels that in turn might play a role in the mechanisms of neurodegeneration in LBD.…”
Section: Discussionsupporting
confidence: 93%
“…1A,B), the initial two curved helical N-terminal domains (helices N and C) of a-syn transform into three uncurved N-terminal helical structures. The third helical region appears when the second curved helix (aa 46-84) converts into two uncurved helices, helix 2 (aa [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] and helix 3 (aa 74-84), linked by aa [64][65][66][67][68][69][70][71][72][73] (Fig. 1A,B).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that intracellular ␣-syn does not contribute under these experimental conditions to the pore formation, although other studies have shown that cells expressing mutant ␣-syn[A53T] have a higher plasma membrane permeability (Furukawa et al, 2006).…”
Section: Discussionmentioning
confidence: 69%
“…1). In solution and at high concentrations (Ͼ200 M), ␣-Syn spontaneously forms annular pore-like structures (20,21) that, when added externally to the culture medium, can cause toxic ion leakage in neuroblastoma cells (22).…”
mentioning
confidence: 99%